Hemofiltration and Hemodialysis in the Prevention and Treatment of Acute Renal Failure after Cardiac Surgery under Extracorporeal Circulation - E. A. Tabakyan; S. A. Partigulov; T. N. Savushkina; M. G. Lepilin; R. S. Akchurin (Общая реаниматология, 2012)
Objective: to analyze the efficiency of hemofiltration (HF) in the stage of extracorporeal circulation (EC) during cardiac surgery in order to prevent acute renal function lowering and the development of acute renal failure (ARF). Materials and methods. The risk of postoperative ARF requiring renal replacement therapy (RRT) was preoperatively assessed by the summed Cleveland risk score and percentage (2005). HF during EC was used in patients at high risk for ARF. The procedure was performed, by combining 2 extracorporeal circuits: EC and a Diapact®CRRT apparatus. With evolving ARF, Stage 3 after Risk, Injury, Failure, Loss of Kidney Function, End-stage Renal Disease (RIFLE), 2004, and Acute Kidney Injury Network (AKIN), 2007, continuous venovenous hemofiltration (CVVHF) and continuous high-flow hemodialysis (CHFHD) were done in the dialysate recirculation mode after surgery under EC. The Mann-Whitney non-parametric test was used to estimate the significance of intergroup differences. The results are presented: median (lower quartile; upper quartile), the differences considered to be significant atpResults. HF during EC; 6 patients were aged 65.5 (range 57—70) years with chronic kidney disease, preoperative glomerular filtration rate (GFR) was 50 (range 41.5—65) ml/min/1.73 m2 using the Cockroft-Gault formula. The maximum GFR decrease by 2.9 (range 0.7—7) ml/min/1.73 m2 was seen after EC. A control group comprised 12 patients aged 73 (range 63—75) years. There was a postoperative GFR reduction by 17 (range 13.7—22) ml/min/1.73 m2. One patient from the control group developed ARF and multiple organ dysfunction, which required CVVHF and CHFHD. Conclusion. The use of intraoperative HF in patients at high risk for renal function lowering is likely to prevent a considerable GFR reduction and ARF after surgery under EC.